Konseling Individual untuk Meningkatkan Daya Tangkap Disabilitas Fisik dalam Refreshing Up Grading - muhammad ilyas ilyas (Irsyad : Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2020)
Individual counseling is one of technique that serves to alleviate problems which faced by individuals in order to be able to adjust to the environment. The techniques carried out in this study include attending, empathy, reflection, exploration, and paraphrasing. The material used in giving this treatment is playing Nine Values “Sembilan Nilai” ​​(SEMAI) and screening short films. This study aims to determine the effectiveness of individual counseling to increase the ability to capture persons with physical disabilities in a refreshing up grading program at the Center for Social Rehabilitation of Persons with Physical Disabilities Prof. Dr. Soeharso Surakarta. This study uses an experimental method type one group post test design. The subjects of this study were 5 persons with physical disabilities who participated in the refreshing up grading program using total sampling techniques. The subjects in this study were selected according to the specified inclusion characteristics. While data collection techniques in the form of observation check list, Progressive Standard Test Matrices,and Minnesota Expose Form Board Test, and documentation. The data analysis used in this study is the Paired Samples Test. The results of the data analysis revealed that the calculated value for individual counseling was 2.738 with probability (Sig.) .052, which meant that there was no significant effect of individual counseling on the ability to capture persons with physical disabilities. This is supported by the results of observations of the capture power checklist that shows the results of observations of capture power aspects as well as results from the Minnesota Expose Form Board Test which shows the perceptions of persons with physical disabilities.